Synthesis, characterization, and field-effect properties of (E)-2-(2-(thiophen-2-yl)vinyl)thiophen-based donor–acceptor copolymers. (26th June 2015) - Wang, Liping; Xie, Xiaodong; Shi, Shaowei; Shi, Keli; Mao, Zupan; Zhang, Weifeng; Wang, Haiqiao; Yu, Gui
Abstract: Two donor–acceptor copolymers, PTVTBT and PTVTBO, using the highly π -extended ( E )-2-(2-(thiophen-2-yl)vinyl)thiophen as an electron-rich unit and benzodiathiazole or benzoxadiazole as an electron-deficient one, were designed and synthesized via a Pd-catalyzed Stille-coupling method. The copolymers possess high thermal stability, broad absorption, low band gap, and good film-forming ability. Meanwhile the two polymers exhibit excellent hole transport properties when used as the active layer in polymer field-effect transistor devices. The highest hole mobility can reach to 0.25 and 0.50 cm 2  V −1  s −1 for the PTVTBT and PTVTBO thin films, respectively. This work demonstrates that PTVTBT and PTVTBO would be promising semiconductors for developing cost-effective and large-scale production of flexible organic electronics. Graphical abstract: Highlights: ( E )-2-(2-(thiophen-2-yl)vinyl)thiophen-based donor–acceptor copolymers were synthesized. Both polymers exhibit good solubility and solution processability. Thin-film transistors show hole transporting properties. The highest hole mobility reaches to 0.5 cm 2  V −1  s −1 under ambient conditions. The annealing treatment has a large effect on the device performance.